Pupil health and educational attainment: Examining the impact of pupil physical and mental health on GCSE outcomes in Northern Ireland. - Early, Erin; Miller, Sarah; Dunne, Laura; O'Reilly, Dermot (International Journal of Population Data Science, 2026)
Educational outcomes are affected by pupils’ physical and mental health, however, there is limited analysis of how attainment is affected by pupils’ health status in Northern Ireland (NI). This study explores the impact of pupils’ physical and mental health on post-primary attainment in NI using population-wide data. Using administrative data that linked the household Census (2011), School Leavers Survey and School Census for the first time in NI, the associations between pupils’ GCSE outcomes, their physical health and mental health were examined (n=61,373). Three variables measured pupils’ physical health (self-reported health status, presence of a limiting illness/disability and presence of a physical condition) and one variable measured the presence of a mental health condition. Multilevel models accounted for the nested data structure and wider demographic profile of pupils. The study found that pupils with a physical health condition (d=-0.39, 95% CI:-0.41, -0.36) or a mental health condition (d=-0.91, 95% CI:-1.00, -0.82) achieved lower GCSE outcomes. The negative association between poorer health and GCSE attainment was also evident among pupils reporting their health as ‘very bad’ (d=-1.01, 95% CI:-1.26, -0.75), and those with an illness/disability that limited daily activity a lot (d=-0.98, 95% CI:-1.04, -0.92). This is the first instance of examining the influence of pupils’ health on their education attainment in NI using linked administrative data. The study highlights the significant role of physical and mental health, reaffirming the importance of viewing health through a holistic lens to understand its full impact on education.